1996
DOI: 10.1118/1.597733
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and calculation of heterogeneity correction factors for an Ir‐192 high dose‐rate brachytherapy source behind tungsten alloy and steel shields

Abstract: Shields made of high atomic number material are commonly used in vaginal applicators with high dose-rate (HDR) 192Ir remotely afterloaded brachytherapy sources. However little data is available for the dose distribution around such shields. Heterogeneity correction factors (HCFs) are defined as the ratio of the dose to a point with the heterogeneity (shield) in place, divided by the dose to the same point with no heterogeneity. Using thermoluminescent dosimeters (TLDs) in solid water phantom we have measured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…In addition, the precision of RCF response ͑95% confidence interval of Ϯ1%-2% for a single 100 mϫ100 m pixel measurement over the 15-60 Gy dose range͒ is far superior to the TLD dosimetry precision ͑2% for a 3ϫ3ϫ0.9 mm 3 TLD with 3-5 separate readings͒ achieved in our laboratory. 8,9 Due to experimental uncertainties not controlled by our methods, e.g., positional uncertainties, leakage of radioactivity and film damage from trimming, errors significantly larger than 5% occur within 4 mm of physical contact between the balloon surface and the RCF detectors. The 14.5% disagreement between film A and MCPT and 7% for film B ͓Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the precision of RCF response ͑95% confidence interval of Ϯ1%-2% for a single 100 mϫ100 m pixel measurement over the 15-60 Gy dose range͒ is far superior to the TLD dosimetry precision ͑2% for a 3ϫ3ϫ0.9 mm 3 TLD with 3-5 separate readings͒ achieved in our laboratory. 8,9 Due to experimental uncertainties not controlled by our methods, e.g., positional uncertainties, leakage of radioactivity and film damage from trimming, errors significantly larger than 5% occur within 4 mm of physical contact between the balloon surface and the RCF detectors. The 14.5% disagreement between film A and MCPT and 7% for film B ͓Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The authors just mentioned that photons with energies equal to or higher than 1 MeV exhibited a significant electronic buildup effect over a distance of 1 mm from the point source. In our opinion, the studies by Valicenti et al 11 and Nath et al 12 should not be considered for approximating collision kerma to absorbed dose for the stainless steel encapsulated 137 Cs sources. Similarly, the work by Kirov et al.…”
Section: Introductionmentioning
confidence: 94%
“…Although the published studies by Valicenti et al, 11 by Kirov et al, 12 and by Nath et al 13 have limitations, these studies are often cited while approximating collision kerma to absorbed dose for the stainless steel encapsulated 137 Cs brachytherapy sources. For example, Pérez-Calatayud et al 7,9,14 referred to the work by Nath et al 13 and Williamson 3 referred to the work by Valicenti et al 11 and by Kirov et al 12 Based on Roesch's work, 15 Valicenti et al 11 evaluated dose to water-kerma ratio D / K for a 400 keV point photon source in water and found that the ratio is less than 1.01 for distances greater than 2 mm from the source. The EGS4-based 16 Monte Carlo study by Kirov et al 12 is devoted to D / K in water for small photon sources ͑including point sources͒ such as 137 Cs, 60 Co, and 24 Na.…”
Section: Introductionmentioning
confidence: 99%
“…Some applicators containing local shielding to spare bladder and rectal tissues can produce dose reductions as large as 50% 103,104 that most treatment planning systems still continue to ignore. The perturbing effects of partial transmission shielding have been shown 73,105,106 to vary rapidly with cross-sectional area and location of shielding materials, especially for sources with energies at or below that of 192 Ir. Only for 137 Cs shielded sources can one-dimensional pathlength algorithms ͑available on some commercial planning systems͒, e.g., generalizations of the Sievert integral model, 107 be used reliably.…”
Section: Iie Accounting For Heterogeneities In Dose Calculationsmentioning
confidence: 99%